2016
DOI: 10.1007/s10853-016-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon particle pinhole defects in aluminium–silicon alloys

Abstract: It was recently shown that silicon particles in heat-treated Al-Si casting alloys can contain flaws such as surface pinholes and grooves, which cause varying degrees of reduction in the in situ particle fracture strength and hence influence the mechanical properties of this class of alloys. In this work, we show that the formation of one class of such strength-limiting flaws in solidified and coarsened Si particles, namely surface pinholes, is caused by alloy impurities such as Fe and Ti in both binary eutecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Selective dissolution of primary aluminium phases over a depth of a few micrometers creates the pinholes [39]. The images prove that there are localized corrosion and discrete pits on the surfaces of the samples.…”
Section: Sem and Edx Observationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Selective dissolution of primary aluminium phases over a depth of a few micrometers creates the pinholes [39]. The images prove that there are localized corrosion and discrete pits on the surfaces of the samples.…”
Section: Sem and Edx Observationsmentioning
confidence: 84%
“…Increased surface pinholes can be discerned on the surfaces of the hypereutectic alloy, which may be attributed to intermetallic particles created by high impurity. These surface pinholes indicate an excessive pitting corrosion mechanism [39].…”
Section: Optical Micrographic Investigationmentioning
confidence: 99%
“…As shown in Figure 3g, some Si particles have not begun to fuse after squeezing in the alloy, and there are dents on the surface caused by squeezing with other particles (marked by green arrows). In Figure 3d,h, holes on the Si particles (marked by red arrows) can be seen, these are caused by impurity elements, such as Ti and Fe, and have nothing to do with the evolution of Si particles [23]. The high magnification secondary electron images of the Si particles during the solution treatment are shown in Figure 3, which more intuitively shows the other two evolution mechanisms.…”
Section: Microstructurementioning
confidence: 88%
“…Therefore, it is necessary to determine the action time of each mechanism and formulate a reasonable heat treatment system for Al-Si alloys. The spheroidization of Si particles has been widely demonstrated: the decrease of surface energy is its main driving force, and it usually occurs in a relatively short time (<1 h) [23]. In the following sections, splitting, fusion, and coarsening will be discussed.…”
Section: Microstructurementioning
confidence: 99%
“…Mueller et al also determined that Si particles were weakened by pinhole defects and interfaces visible on their surfaces. They also [110] found Ti-and Fe-rich intermetallics at the bottom of the pinhole defects, embedded in the Si particles, which significantly weakened the particles. In Figure 7, the limits determined by Caceres et al are also indicated, as well as the cumulative probabilities associated with them.…”
Section: Si Particles In Al-si Alloysmentioning
confidence: 95%